Automatic evaluation of the fundamental frequency variations and related damping factor of reinforced concrete framed structures using the Short Time Impulse Response Function (STIRF). (1st January 2015) - Ditommaso, R.; Ponzo, F.C.
Highlights: STIRF to analyze the time-varying behavior of a framed structure under seismic strong motion. Automation of fundamental frequency evaluation during a strong motion earthquake. Upgrade of some existing methods for damage detection on critical structures. Abstract: Structural Health Monitoring (SHM) aims to improve knowledge of the safety and maintainability of civil structures and infrastructures. This paper presents an innovative strategy for automatic evaluation of the variable fundamental frequency and related damping factors of nonlinear structures during strong motion phases. In fact, most of methods for damage detection are based on the assessment of the variations related to dynamic parameters characterizing the monitored structure. In this case, a crucial aspect is a correct estimation of both structural eigenfrequencies and related damping factor also during the nonlinear behavior of a monitored structure. In this paper, nonlinear interferometric analyses combined with the Fourier Transform (FT) are proposed to evaluate the Short-Time Impulse Response Function (STIRF) able to characterize frequencies and damping variations of a monitored structure. Two application of the STIRF are proposed on both numerical and experimental models.